2018
DOI: 10.1002/hep.29911
|View full text |Cite
|
Sign up to set email alerts
|

Liver Angiopoietin‐2 Is a Key Predictor of D e N ovo or Recurrent Hepatocellular Cancer After Hepatitis C Virus Direct‐Acting Antivirals

Abstract: Recent reports suggested that direct acting antivirals (DAAs) might favor hepatocellular carcinoma (HCC). In study 1, we studied the proangiogenic liver microenvironment in 242 DAA‐treated chronic hepatitis C patients with advanced fibrosis. Angiopoietin‐2 (ANGPT2) expression was studied in tissue (cirrhotic and/or neoplastic) from recurrent, de novo, nonrecurrent HCC, or patients never developing HCC. Circulating ANGPT2,vascular endothelial growth factor (VEGF), and C‐reactive protein (CRP) were also measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
125
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(138 citation statements)
references
References 36 publications
12
125
1
Order By: Relevance
“…All these characteristics (advanced age, comorbidities, and high burden of comedications) could potentially affect tolerability of HCV treatment and adherence in this subgroup [7]. Moreover, some possible side effects and biomarker alterations, as well as increased risk of liver cancer, have been reported by several authors, especially in elderly people [8][9][10][11][12][13]. In addition, the presence of some side effects was in particular reported among those who had concurrent comorbidities (such as liver cirrhosis, cardiac failure, and advanced age) [14,15].…”
Section: Introductionmentioning
confidence: 95%
“…All these characteristics (advanced age, comorbidities, and high burden of comedications) could potentially affect tolerability of HCV treatment and adherence in this subgroup [7]. Moreover, some possible side effects and biomarker alterations, as well as increased risk of liver cancer, have been reported by several authors, especially in elderly people [8][9][10][11][12][13]. In addition, the presence of some side effects was in particular reported among those who had concurrent comorbidities (such as liver cirrhosis, cardiac failure, and advanced age) [14,15].…”
Section: Introductionmentioning
confidence: 95%
“…Interestingly, a signature of five genes (angiopoietin‐2 [ ANGPT2 ], delta‐like ligand 4 [ DLL4 ], neuropilin/tolloid‐like 2 [ NETO2 ], endothelial cell‐specific molecule‐1 [ ESM1 ], and nuclear receptor subfamily 4, group A, member 1 [ NR4A1 ]), all related to angiogenesis, characterized a subset of highly aggressive and fast‐growing HCC at onset . It is therefore likely that vascular pattern heterogeneity can also play a role in tumor progression . Interestingly, Fang et al reported a distinct pattern of HCC vascularization that predicted rapid tumor dissemination and high recurrence rates .…”
mentioning
confidence: 99%
“…(9) It is therefore likely that vascular pattern heterogeneity can also play a role in tumor progression. (10) Interestingly, Fang et al reported a distinct pattern of HCC vascularization that predicted rapid tumor dissemination and high recurrence rates. (11) This pattern is characterized by the presence of CD34 + vessels completely encapsulating tumor clusters (VETC).…”
mentioning
confidence: 99%
“…They also showed that angiopoietin-2 expression in HCC and cirrhotic tissue before DAAs treatment relates to the risk of HCC recurrence and occurrence. 331 Recently, we reported that HCC developed in the cirrhotic liver when the hepatic adaptive response reprogrammed to switch from prodeath to the pro-survival state through autophagy switching. In addition, our laboratory illustrated that virus-associated ER stress and tumor suppressor loss (p53 and Rb, miR-122 levels) were restored more by IFN-induced HCV clearance than DAAs in cell culture models.…”
Section: Reversal Of Direct Mechanisms After Daas Treatmentmentioning
confidence: 99%